STUDENTS' LEARNING STRATEGIES IN ACCOMPLISHING WRITING TASKS - Hilaliah, Nur (2017)
This study entitled "Student's Learning Strategies in Accomplishing Writing Tasks" was aimed at revealing learning strategies used by second year EFL university students' in completing writing tasks and their considerations in selecting the strategies. This study employed a descriptive qualitative research design. A class of 33 second-year university students in one public university in Bandung was selected as participants of this study. Questionnaire and interviews were used as data collection techniques. Two types of questionnaires were employed; a closed-ended (Likert scale questionnaire) and an open-ended questionnaire. The data from the closed-ended questionnaire were analyzed using descriptive statistics to depict the general tendency of the strategies use, whereas the data from the open-ended questionnaire and the interview were firstly divided into pre, whilst and post writing strategies then were classified according to Oxford's (1990) classification of Language Learning Strategies. The results showed that the respondents in this study were active users of language learning strategies. The most frequently used strategies were social and cognitive strategy categories. Meanwhile, the individual strategies found to be the most frequently used among the respondents were resourcing (cognitive), getting feedback (social) and using synonyms and circumlocution (compensation). Moreover, the results also suggested that in selecting the strategies, the respondents considered the topic and the text type, the readers of the text and the time efficiency. Finally, the results of this study provide EFL students with a range of strategies useful in accomplishing writing tasks and could also be used as consideration for teachers in designing instructional planning for teaching writing which can accommodate students' preference of strategies.;--- Penelitian yang berjudul "Strategy Belajar Siswa dalam Menyelesaikan Tugas Menulis" ini bertujuan untuk mengungkap strategi yang digunakan mahasiswa Bahasa Inggris tahun kedua dalam meyelesaikan tugas menulis dan pertimbangan mereka dalam memilih strategi tersebut. Penelitian ini menggunakan desain penelitian deskriptif kualitatif dengan angket dan wawancara digunakan sebagai teknik pengumpulan data. Responden dalam penelitian ini ialah satu kelas berisi 33 mahasiswa tingkat dua pada salah satu universitas negeri di Bandung. Dalam penelitian ini. dua macam angket digunakan yakni angket tertutup dan angket terbuka. Data dari angket tertutup dianalisis menggunakan deskriptif statistik demi menggambarkan tendensi umum penggunaan strategi belajar. Sedangkan data dari angket terbuka dan wawancara dianalisis dengan pertama-tama mengkategorkan data ke dalam pre-, whilst-, dan post-writing strategies, kemudian data diklasifikasikan berdasarkan klasifikasi Strategi Belajar Bahasa Oxford. Hasil penelitian ini menunjukkan bahwa responden dalam penelitian ini merupakan pengguna aktif terhadap strategi belajar. Kategori strategi yang paling banyak digunakan adalah kategori strategi sosial dan kognitif. Sementara, strategi individu yang paling banyak digunakan adalah resourcing (cognitif), getting feedback (sosial) dan using synonyms and circumlocution (compensasi). Hasil penelitian ini juga menunjukkan bahwa dalam memilih strategi untuk digunakan, responden mempertimbangkan topik dan jenis teks yang ditugaskan, pembaca teks tersebut dan efisiensi waktu. Selanjutnya, hasil dari penelitian ini diharapkan mampu memberikan gambaran kepada pembelajar Bahasa Inggris mengenai strategi belajar yang dapat digunakan dalam menyelesaikan tugas menulis dan diharapkan pula dapat berguna sebagai salah satu bahan pertimbangan dalam mendesain rencana pembelajaran untuk pengajaran kemampuan menulis yang dapat mengakomodasi preferensi strategi siswa.